Junctionless nanosheet gate‐all‐around transistors fabricated on void embedded silicon on insulator substrate. Issue 4 (18th February 2023) - Mu, Zhiqiang; Zhou, Hongyang; Yang, Yumeng; Liu, Qiang; Wei, Xing; Yu, Wenjie
Abstract: A novel junctionless gate‐all‐around (GAA) transistor with ultrathin nanosheet GAA channel and self‐aligned raised source/drain (RSD) is successfully designed and fabricated on void embedded silicon on insulator (VESOI) substrate through a much simpler fabrication process. Devices with as thin as 13‐nm nanosheet GAA channel thickness exhibit excellent electrical characteristics: on/off current ratio of 10 6 and on‐state drive current of 58 µA/µm. Although the parasitic planar channel component still exists, the device performance is decisively dominated by the GAA channel, and further boosted by the junction‐free bulk conduction mechanism and the self‐aligned RSD structure. Abstract : A novel junctionless gate‐all‐around (GAA) transistor with ultrathin nanosheet GAA channel and self‐aligned raised source/drain (RSD) is successfully designed and fabricated on void embedded silicon on insulator (VESOI) substrate through a much simpler fabrication process. Devices with as thin as 13 nm nanosheet GAA channel thickness exhibit excellent electrical characteristics: on/off current ratio of 10 6 and on‐state drive current of 58 µA/µm.